"Plasma exchange in a bottle": An overview of efgartigimod for apheresis practitioners. Issue 5 (23rd August 2022) - Tran, Minh‐Ha
Abstract: Efgartigimod represents a first‐in‐class immunomodulatory agent that is comparable to TPE in reducing immunoglobulin levels. This translates to reductions in Myasthenia Gravis symptom scores with maximal effect following the fourth weekly efgartigimod dose. Efgartigimod received FDA approval in December of 2021 and may be an alternative particularly for patients on long‐term TPE regimens of weekly or less frequent. Apheresis practitioners, especially those managing long‐term apheresis in seropositive individuals, may therefore see some of their patients transitioned from plasma exchange to efgartigimod. Long‐term experience with efgartigimod remains lacking and studies are needed to establish the role of efgartigimod in the acute setting.